2018
DOI: 10.1186/s13071-018-3192-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of tick-borne pathogens in canine population and Rhipicephalus sanguineus (sensu lato) ticks from southern Metro Manila and Laguna, Philippines

Abstract: BackgroundThe tropical climate of the Philippines and the high population of dogs, particularly in cities, favors the life-cycle of the brown dog tick, Rhipicephalus sanguineus (sensu lato), a vector of several canine tick-borne pathogens (TBPs) including zoonotic Rickettsia spp. Suspected cases of infections are commonly encountered in veterinary clinics, but the specific TBPs are rarely identified. Furthermore, infection with Rickettsia is not being clinically examined in dogs. In this study, the occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 36 publications
7
50
1
4
Order By: Relevance
“…Recently, our group detected Rickettsia in dogs from Laguna, one of the provinces in this study, through the same nested PCR employed in this study. It was found that the amplicons were highly identical to R. japonica after sequence analysis [33].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, our group detected Rickettsia in dogs from Laguna, one of the provinces in this study, through the same nested PCR employed in this study. It was found that the amplicons were highly identical to R. japonica after sequence analysis [33].…”
Section: Discussionmentioning
confidence: 96%
“…Camer et al [31] demonstrated the presence of antibodies against the SFG and TG Rickettsia and C. burnetii in humans by indirect immunofluorescent antibody test (IFAT), whereas Cardona [32] used complement fixation for serological testing of C. burnetii in domestic ruminants and humans. Recently, a study from our group utilizing nested PCR provided evidence for the presence of Rickettsia in dogs in the Philippines [33]. Here, we investigate the presence of Rickettsia and C. burnetii in cattle and water buffalo, as well as R.…”
Section: Introductionmentioning
confidence: 99%
“…Tick-borne diseases are a common problem worldwide and has increase in their importance due to the capability of causing critical illness as well as possibility of death in infected human and animals [1][2][3]. Tick-borne haemopathogens (TBH) were closely related to the companion animals which act as resevoir of the various pathogen but also a potential victim that could harm this cats and dogs [4].…”
Section: Malaysia Backgroundmentioning
confidence: 99%
“…sanguineus s.l. This protozoan is commonly found in dogs in Thailand, Taiwan, China, Cambodia, Malaysia, Philippines and Vietnam [10, [17][18][19][23][24][25] and in cats in Thailand and Philippines [10,23]. Of the tick-borne anaplasmatacea bacteria, Anaplasma platys was found in dogs from Cambodia [18] and cats from Thailand [26].…”
Section: Ehrlichia Canis Rickettsia Conorii Rickettsia Rickettsia mentioning
confidence: 99%